Internists’ ambivalence toward their role in health counseling and promotion: A qualitative study on the internists’ beliefs and attitudes - Kromme, Nicolien M. H.; Ahaus, Kees T. B.; Gans, Reinold O. B.; van de Wiel, Harry B. M. (PLOS ONE, 2022)
Crucial to its success is that physicians enhance their competence in Lifestyle Medicine and take on their role as Health Advocates in Health Counseling and Promotion (HC&P). However, studies on patients’ views of lifestyle counseling in clinical practice demonstrate that many patients neither perceived a need to adopt a healthy lifestyle nor having had any discussion with their physician about their lifestyle. This study is part of a participatory action research project focusing on identifying areas of improvement for health promotion in the practice of internists. Within this project, we interviewed 28 internists from six different subspecialties of an academic medical center in the Netherlands. This study aims to gain insight into how internists understand their role in HC&P by a qualitative analysis of their beliefs and attitudes in the interview data. Participants claimed that promoting a healthy lifestyle is important. However, they also reflected a whole system of beliefs that led to an ambivalent attitude toward their role in HC&P. We demonstrate that little belief in the success of HC&P nurtured ambivalence about the internists’ role and their tasks and responsibilities. Ambivalence appeared to be reinforced by beliefs about the ability and motivation of patients, the internists’ motivational skills, and the patient-doctor relationship, and by barriers such as lack of time and collaboration with General Practitioners. When participants viewed HC&P as a part of their treatment and believed patients were motivated, they were less ambivalent about their role in HC&P. Based on our data we developed a conceptual framework that may inform the development of the competences of the Health Advocate role of internists in education and practice.